2018
DOI: 10.1038/s41598-018-33478-9
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Assessment of Human and Chimpanzee iPSC-derived Cardiomyocytes with Primary Heart Tissues

Abstract: Comparative genomic studies in primates have the potential to reveal the genetic and mechanistic basis for human specific traits. These studies may also help us better understand inter-species phenotypic differences that are clinically relevant. Unfortunately, the obvious limitation on sample collection and experimentation in humans and non-human apes severely restrict our ability to perform dynamic comparative studies in primates. Induced pluripotent stem cells (iPSCs), and their corresponding differentiated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 82 publications
2
79
0
Order By: Relevance
“…We previously collected RNA sequencing data from the same human and chimpanzee iPSC lines [61]. We jointly analyzed the Hi-C and RNA-sequencing data to learn how often inter-species differences in 3D genomic contact frequencies are associated with inter-species differences in gene expression.…”
Section: The Relationship Between Inter-species Differences In Contacmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously collected RNA sequencing data from the same human and chimpanzee iPSC lines [61]. We jointly analyzed the Hi-C and RNA-sequencing data to learn how often inter-species differences in 3D genomic contact frequencies are associated with inter-species differences in gene expression.…”
Section: The Relationship Between Inter-species Differences In Contacmentioning
confidence: 99%
“…We considered our Hi-C data along with gene expression data previously collected from the same cell lines [61] and assessed the extent to which inter-species variation in 3D genome contacts could potentially explain gene expression divergence between species. Previous studies have observed that spatial co-expression of genes is associated with chromatin interaction profiles [26,30,31,41,76].…”
Section: Contribution Of Variation In 3d Genome Structure To Expressimentioning
confidence: 99%
See 2 more Smart Citations
“…The 93 availability of suitable samples from chimpanzees has notoriously been a limitation for 94 130 Using a linear model framework (see Methods), we identified 8,880 differentially 131 expressed (DE) genes between species (FDR<0.05; TableS2), including 6,409 DE genes with 132 effect sizes smaller than a twofold change (FigS2). As our comparative sample size is unusually 133 large, we have an opportunity to comment on the robustness of observations that are made using 134 study designs with smaller sample sizes, which are more typical for comparative studies in 135 primates (Khan et al, 2013;Pavlovic et al, 2018;Perry et al, 2012 (Göring et al, 2001;Ioannidis, 2008), which particularly affect under-powered 159 study designs (FigS3E). However, even at this small sample size, the false positive rate 160 associated with the classification of DE genes is well calibrated; when we used an FDR of 5% to 161 classify genes as DE between the species, we empirically estimated a median of 2% (1 -5% 162 IQR) false discoveries based on the gold standard reference.…”
Section: Introduction 16mentioning
confidence: 99%